2019
DOI: 10.1007/s00442-019-04522-w
|View full text |Cite
|
Sign up to set email alerts
|

Does a bigger mouth make you fatter? Linking intraspecific gape variability to body condition of a tropical predatory fish

Abstract: In gape-limited predators, gape size restricts the maximum prey size a predator is capable to ingest. However, studies investigating the energetic consequences of this relationship remain scarce. In this study we tested the hypothesis that gape-size variability influences individual body condition (a common proxy for fitness) in one of the largest freshwater teleost predators, the barramundi. We found that individual barramundi with larger gapes relative to body size had higher body condition values compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Previous isotopic food web research found little evidence of remote floodplain carbon in fish inhabiting dry season pools in the Fitzroy River (Jardine, Pettit, et al., 2012); however, that study did not examine large‐bodied fish species. We posit that wet season floodplain inundation is most important for the dry season energetics of large species, such as fork‐tailed catfish and barramundi ( Lates calcarifer ), which have the capacity to store large amounts of fat in their body cavity (see Luiz et al., 2019). These species move into floodplain habitats to forage in other northern Australian rivers (Crook et al., 2019; Pusey et al., 2020), and in the Fitzroy River, we expect them to take advantage of wet season production and potentially link floodplain and main‐channel food webs (Jardine, Pusey, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous isotopic food web research found little evidence of remote floodplain carbon in fish inhabiting dry season pools in the Fitzroy River (Jardine, Pettit, et al., 2012); however, that study did not examine large‐bodied fish species. We posit that wet season floodplain inundation is most important for the dry season energetics of large species, such as fork‐tailed catfish and barramundi ( Lates calcarifer ), which have the capacity to store large amounts of fat in their body cavity (see Luiz et al., 2019). These species move into floodplain habitats to forage in other northern Australian rivers (Crook et al., 2019; Pusey et al., 2020), and in the Fitzroy River, we expect them to take advantage of wet season production and potentially link floodplain and main‐channel food webs (Jardine, Pusey, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study is one of the few to investigate the link between fish energy stores and flow/water availability in northern Australian rivers (but see Luiz et al., 2019 and Lear et al., 2020); however, its inference is limited by the short term nature of the datasets examined. The association between energy stores and wet season flow in the Fitzroy River is indirect and asserted via inter‐annual patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations